Pioneering the I-COPE Model: Integrating Outcomes-Based Education, Ignatian Pedagogical Paradigm, and 5Es Inquiry Framework in Pre-Service Teacher Education for Technology Integration - Ronald M. Quileste (Journal of Education and Teaching (JET), 2025)
This mixed-methods study evaluated the pioneering I-COPE model, integrating Outcomes-Based Education (OBE), Ignatian Pedagogical Paradigm (IPP), and the 5Es inquiry framework, in ED 11 - Educational Technology 1 at Xavier University – Ateneo de Cagayan, Philippines, during the 2024–2025 academic year. Fifty pre-service teachers participated, with data collected through surveys, pretest/posttest assessments (N = 44), seatwork, and semi-structured interviews (N = 10 per term). A Wilcoxon signed-rank test revealed significant academic improvement (Z = -3.421, p < .001, r = -0.621), driven by OBE’s structured outcomes. Midterm surveys indicated moderate engagement (26–28% positive responses, Mdn = 3.70–3.80), while final surveys showed strong feedback (60–70% positive, Mdn = 4.00), reflecting 5Es’ inquiry and IPP’s reflective practices. Interview themes, including Cognitive Engagement and Holistic Growth, and strong inter-domain correlations (r_s = 0.721–0.945) confirmed I-COPE’s synergistic impact. Weak survey-seatwork correlations (r_s = 0.003–0.105) suggest assessment refinements. As the first evaluation of I-COPE in a Philippine Jesuit context, this study aligns with CHED’s OBE mandates and PPST’s technology competencies, offering a groundbreaking model for teacher education (Barrot, 2020; Lucas, 2020). Recommendations include diversified tasks and clearer 5Es guidance to enhance scalability.